LABORATORY DIAGNOSTICS OF HEPATITIS C VIRUS - Khuzhakulov Davron Abdikhakimovich (TADQIQOTLAR.UZ, 2024)
Annotation. The hepatitis C virus causes an anthroponotic infection with a parenteral transmission mechanism and predominant liver damage. It often occurs in the form of post-transfusion hepatitis with a predominance of anicteric forms and is prone to chronicity. Hepatitis C is called the “gentle killer” because of its ability to mask the true cause under the guise of many other diseases. The causative agent of the disease is the hepatitis C virus. The acute infectious form is asymptomatic in 70-90%, becoming chronic in 60-80%. Globally, approximately 71 million people are chronically infected with hepatitis C virus and are at risk of developing cirrhosis and/or liver cancer. Every year, more than 350 thousand people die from hepatitis C-related liver disease. Every year, 3-4 million people become infected with the hepatitis C virus. Today, 8 genotypes of the virus are known, divided into over 100 subtypes. The source of infection is patients with active hepatitis C and latent patients who are carriers of the virus. HCV infection is an infection with a parenteral mechanism of infection - through infected blood and its components. Infection is possible during parenteral manipulations, including in medical institutions, including the provision of dental services, through injection equipment, during acupuncture, piercing, tattooing, and during the provision of a number of services in hairdressing salons. In 20% of cases, it is not possible to establish the mode of transmission of the virus. Timely detection of infection, as well as control of the course of the disease, is carried out using highly effective laboratory diagnostic methods. The most dangerous, from a source point of view, are patients with chronic hepatitis C.